CHEERS results from NGC 3393 : III. Chandra x-ray spectroscopy of the narrow line region - Maksym, W. Peter (2019)
We present spatially resolved Chandra narrow-band imaging and imaging spectroscopy of NGC 3393. This galaxy hosts a Compton-thick Seyfert 2 active galactic nucleus (AGN) with sub-kpc bipolar outflows that are strongly interacting with the circumnuclear gas. We identify narrow-band excess emission associated with the Ne IX 0.905 keV transition (with likely contributions due to intermediate-state iron emission) that points to strong shocks driven by AGN feedback. Imaging spectroscopy resolves outflow-interstellar medium (ISM) interaction sites and the surrounding ISM at ∼ 100 pc scales, and suggests the presence of a hot AGN wind above the plane at radii beyond the shock sites. The cross-cone shows evidence for reprocessing of photoionization that has passed through gaps in the torus, and also for collisionally excited plasma that may be powered by a shock-confined equatorial outflow. Deep X-ray observations at subarcsecond resolution (such as may be performed very efficiently by Lynx, which would also energetically resolve the complex line emission) are necessary to eliminate model degeneracies and reduce uncertainties in local feedback properties.